If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying g + -19 = 58 Reorder the terms: -19 + g = 58 Solving -19 + g = 58 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '19' to each side of the equation. -19 + 19 + g = 58 + 19 Combine like terms: -19 + 19 = 0 0 + g = 58 + 19 g = 58 + 19 Combine like terms: 58 + 19 = 77 g = 77 Simplifying g = 77
| 28+d=36 | | F/4=2/3 | | .0004-.01b+b=.00015 | | 6x-12=24-3x | | 8x-144=15 | | 6x+11=11x-34 | | 3h+2p=26 | | 1+2b=b-1-3 | | 0.25x=29.5 | | 8x-9=6x-19 | | 9x+9=12x+12 | | 58n=172 | | 40000a+200b=6 | | a-18=22 | | 172=58n | | 3xover+8=5 | | 2.3x^2-1.9x=6.8 | | -4x+-12=2x+24 | | -2(4g)= | | 10000a+100b+4.7=8.7 | | 3/x-2/y | | .25x^2+x=-1 | | 13x-4=12x-6 | | 5x+1=2.2 | | 112-15=b | | 13x-7=5x-47 | | 12x+10=5x+24 | | 3x-12=9x-72 | | 9x+4=5.8 | | S/6-12=-16 | | 2+r=5 | | 3.3x+5.7y-6.7=0 |